A STRENGTHS OF THE TAQWA CURRICULUM MODEL: EVIDENCE FROM HOMESCHOOLING TAHFIDZ SULAIMAN BALADIL HUFFAADZ BANDUNG - Aminah, Aam; Suhardini, Asep Dudi; Rachmah, Huriah (Penerbit Lafadz Jaya, 2026)
This study aims to evaluate the effectiveness and implementation dynamics of the Taqwa Curriculum Model within the context of Islamic homeschooling. The research was conducted at Tahfidz Homeschooling Sulaiman Baladil Huffaadz Elementary School in Bandung over a period of 61 days, utilizing a qualitative case study approach. A total of 17 participants, selected from among teachers and students, were involved in semi-structured interviews. Data were analyzed using a six-step thematic analysis technique. The results indicate that the Taqwa Curriculum Model effectively integrates Al-Qur’an memorization with religious understanding and student character development, which is significantly mediated by active parental involvement through daily Muraja’ah practices. Theoretically, these findings reinforce the concept of Fitrah-based education and the repositioning of the family as the primary educational unit. Practically, the implications emphasize the importance of a supportive learning ecosystem and humanist evaluation methods. Policy recommendations are directed toward the formal recognition of value-based curriculum quality standards within informal education pathways and the provision of structured pedagogical guidelines for parents to ensure the sustained quality of national Islamic education. Further research employing quasi-experimental or longitudinal approaches is recommended to obtain more robust evidence regarding the effectiveness of the Taqwa Curriculum Model.